N‐1 semi‐continuous transient perfusion in shake flask for ultra‐high density seeding of CHO cell cultures in benchtop bioreactors - Lemire, Lucas; Reyes, Sebastian‐Juan; Durocher, Yves; Voyer, Robert; Henry, Olivier; Pham, Phuong Lan (Biotechnology progress, 2025)
One strategy to enhance the production of biological therapeutics is using transient perfusion in the preculture (N-1 stage) to seed the production culture (N stage) at ultra-high cell densities (>10 x 10⁶ viable cells/mL). This very high seeding density improves cell culture performance by shortening the timeline and/or achieving higher final product concentrations. Typically, an N-1 seed train employs bioreactors with alternating tangential flow filtration (ATF) or tangential flow filtration (TFF) perfusion systems or Wave cell bag bioreactor with integrated filtration membrane, which have costs and technical complexity. Here, we propose an alternative method using semi-continuous transient perfusion through media exchange in shake flasks, which is suitable for benchtop-scale intensification process development. Daily media exchange was necessary to prevent nutrient limitations. The observed limitation of maximum viable cell densities (VCD) in various flask sizes was demonstrated to be due to oxygen limitations through the measurements of maximum oxygen transfer rates (OTR) using the sulfite system. By increasing agitation frequency from 200 to 300 RPM, maximum OTR in 500-mL shake flasks was increased by 62.3%, allowing an increase in maximum VCD of 29.6%. However, in 1000-mL shake flasks, an increase in agitation rate resulted in early cell death. After demonstrating that media exchange in shake flasks by centrifugation had no significant impact on cell growth rates, metabolism, and productivity, a benchtop bioreactor was seeded from semi-continuous transient perfusion cell expansion. The ultra-high cell density seeding resulted in a 49.3% increase in space–time-yield (STY) when compared to a standard low seeding density culture.